PENERAPAN MODEL ARCS (ATTENTION, RELEVANCE, CONFIDENCE, SATISFACTION) DALAM PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMK MUARA ILMU DEPOK” - Dede Setiawan; Nur Kabibullah; Imam Sodiqul Wadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2020)
This study aims to find out how to implement the ARCS (Attention, Relevance, Confidence, Satisfaction) motivation model in the learning process. This research is a qualitative research.The results showed that the implementation of the ARCS model (Attention, Relevance, Confidence, Satisfaction) in the study of Islamic Religion at SMK Muara Ilmu Depok, namely; First, the teacher always tries to arouse students' attention to the lesson by using various learning methods. Second, trying to show the relationship of the material learned with the needs of students by expressing learning objectives, benefits and showing the nature of enthusiasm. Third, increase students' confidence in their abilities by providing hope of success, systematic learning arrangement from easy to complicated and sequential material where one material can support the next material, such as the thaharah chapter given first before the prayer chapter and giving feedback that is constructive. Fourth, create student satisfaction by giving praise, giving opportunities to show their abilities, and opportunities to help friends who have not mastered.